Moderate chronic kidney disease and left atrial enlargement independently predict thromboembolic events and mortality in elderly patients with atrial fibrillation: a retrospective single-center study. Issue 9 (September 2019) - Wang, Hai-jun; Li, Kai-liang; Li, Jian; Lin, Kun; Shi, Yang; Wang, Hao; Si, Quan-jin; Wang, Yu-tang
Objective: This study aimed to evaluate the effects of moderate chronic kidney disease (CKD) and left atrial enlargement on the risks of thromboembolic events, and all-cause and cardiovascular mortalities in elderly patients with atrial fibrillation (AF). Methods: We retrospectively studied 751 patients (82.16% men, mean age: 79.0±9.1 years) with AF who were followed up for an average of 34.5 months at a single center. Adjusted hazard ratios (HRs) of risk factors for adverse clinical events were calculated using the Cox proportional hazards model. Results: The risks of thromboembolic events, and all-cause and cardiovascular deaths were higher in patients with moderate CKD compared with patients with normal renal function after adjusting for other traditional risk factors (HR: 1.63, 95% confidence interval (CI): 1.03–2.58; HR: 1.55, 95% CI: 1.08–2.23; HR: 3.49, 95% CI: 1.57–7.74; respectively). Left atrial volume index >28.0 mL/m 2 was an independent risk factor associated with thromboembolic events and all-cause and cardiovascular deaths (HR: 1.62, 95% CI: 1.21–2.33; HR: 1.56, 95% CI: 1.16–2.10; HR: 1.87, 95% CI: 1.07–3.28; respectively). Conclusions: Moderate CKD and left atrial enlargement may predict thromboembolic events, and all-cause and cardiovascular mortalities in elderly patients with AF without anticoagulation therapy.